Dementia and occupational exposure to magnetic fields - Feychting, Maria; Pedersen, Nancy L.; Svedberg, Pia; Floderus, Birgitta; Gatz, M. (Scandinavian Journal of Work, Environment & Health, 1998)
' ' OBJECTIVES ': 'The purpose of the present report was to assess whether occupational magnetic field exposure is a risk factor for dementia, in particular for Alzheimer`s disease ' ' METHODS ': 'Case-control analyses were applied to 77 dementia cases, 55 of whom had Alzheimer`s disease, ascertained from the population-based Swedish twin register. Two reference groups were derived, with 228 and 238 persons, respectively. Occupations were linked to a job-exposure matrix based on magnetic field measurements. Primary occupation, last occupation before reference date, and the occupation with the highest magnetic field exposure during the subject`s lifetime were evaluated ' ' RESULTS ': 'For primary occupation, all relative risk estimates were close to unity. For last occupation, at the exposure level ≥0.2 µT, a relative risk was found for dementia estimated at 3.3 [95% confidence interval (95% CI) 1.3–8.6] and 3.8 (95% CI 1.4–10.2) for reference groups 1 and 2, respectively. The relative risk for Alzheimer`s disease was estimated at 2.4 (95% CI 0.8–6.9) and 2.7 (95% CI 0.9–7.8), respectively. For the occupation with the highest magnetic field exposure, the relative risk estimates were close to unity for reference group 1 and slightly elevated for reference group 2. The relative risk estimates were greater for the subjects who were younger at onset (≤75 years). ' ' CONCLUSION ': 'These results only partially support previous findings, but they indicate that occupational magnetic field exposure may possibly influence the development of dementia.
Keywords: Alzheimer’s disease; case-control study; electromagnetic fields; vascular dementia